Skin Cancer Detection from Smartphone Imagery using Convolutional Neural Network - Dittakan , Kwankamon; Nulek, Piyawat; Prutsachainimmit, Korawit (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2022)
kin cancer is an abnormal growth of human skin cells that develop on the skin being exposed directly to ultraviolet radiation for an extended period of time. It is one of the most common health issues at a rapidly an alarming rate around the world, with 160,000 medical records reported annually. A significant number of records are in Europe, America, and New Zealand. In contrast, the least reported was in Thailand. Moreover, preventing the chance of developing skin cancer is the aim of this research. In this paper, we presented about to detect skin cancer from images using a Convolutional Neural Network (CNN) in one of the models in Deep Learning. In addition, the PAD-UFES-20 datasets are available from the Federal University of Esprito, Federative Republic of Brazil. The accuracy of results was predicted with 81.50% confidence.